2014
DOI: 10.1039/c4ra04927f
|View full text |Cite
|
Sign up to set email alerts
|

On the large capacitance of nitrogen doped graphene derived by a facile route

Abstract: Large level of N-doped graphene prepared by facile route with high supercapacitance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
95
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 167 publications
(105 citation statements)
references
References 43 publications
9
95
1
Order By: Relevance
“…The XRD pattern of rGO shows a (0 0 2) diffraction peak at 25.67° ( d ≈ 0.338 nm), indicating fully exfoliated graphene layers from GO. However, the (0 0 2) diffraction peaks of G–Ni and G–CNT–Ni are slightly shifted and appeared at ≈26° ( d ≈ 0.333 nm), which is close to the value for pristine graphite . The slight lower d‐spacing values of G–Ni and G–CNT–Ni may be due to the additional microwave irradiations.…”
Section: Resultssupporting
confidence: 56%
“…The XRD pattern of rGO shows a (0 0 2) diffraction peak at 25.67° ( d ≈ 0.338 nm), indicating fully exfoliated graphene layers from GO. However, the (0 0 2) diffraction peaks of G–Ni and G–CNT–Ni are slightly shifted and appeared at ≈26° ( d ≈ 0.333 nm), which is close to the value for pristine graphite . The slight lower d‐spacing values of G–Ni and G–CNT–Ni may be due to the additional microwave irradiations.…”
Section: Resultssupporting
confidence: 56%
“…The doping with heteroatoms creates charged sites in the graphene lattice, as a result the spin and charge densities are redistributed bringing new functionalities [16]. In this prospect, nitrogen incorporation in graphene by substitution of carbon atoms has been explored significantly to achieve high electron density, n-type doping, increased capacity of battery, high supercapacitance and oxygen reduction activities [16][17][18][19][20][21][22]. Thus, various studies have revealed that nitrogen doping can be exciting platform to tune or introduce novel properties in graphene.…”
Section: Introductionmentioning
confidence: 99%
“…As we confirm by XPS analysis, the presence of C−N stretching bonds in the N‐doped graphene is exhibits in the sharp peak at 1220 cm −1 and, in the shoulder at 1591 cm −1 . Finally, the presence of C−O groups appears at 1095 cm −1 . From the Raman and FTIR analysis we confirm the coexistence of the Fe 3 O 4 and N‐doped graphene phases as we determined by XRD and XPS study.…”
Section: Resultsmentioning
confidence: 99%